ZEB1 and ZEB2 transcription factors are potential therapeutic targets of canine mammary cancer cells. (25th July 2018) - Xavier, Pedro L. P.; Cordeiro, Yonara G.; Rochetti, Arina L.; Sangalli, Juliano R.; Zuccari, Debora A. P. C.; Silveira, Juliano C.; Bressan, Fabiana F.; Fukumasu, Heidge
Abstract : Mammary tumours are the most frequent in female dogs as in women and half are malignant. Tumorigenicity and invasiveness are important acquired characteristics for the development and progression of cancers and could be regulated by transcription factors associated with epithelial‐mesenchymal transition (EMT) as ZEB1, ZEB2, SNAI1, SLUG and STAT3. Thus, here, we evaluate the expression of EMT‐associated transcription factors in canine mammary cancer (CMC) cell lines characterized for invasiveness and tumorigenicity to determine if these could be considered good targets for future development of therapies. Five CMC cell lines were characterized regarding their morphology, doubling time and expression of intermediate and actin filaments. In addition, gene expression of SLUG, STAT3, ZEB1, ZEB2 and CDH1, tumorigenicity and invasiveness were assessed. Two of these cells presented an epithelial‐like morphology (E20 and E37) and three a mesenchymal‐like morphology (M5, M25 and CF41.Mg). M25 and CF41.Mg presented higher invasiveness. Furthermore, only mesenchymal‐like cells formed tumorspheres and CF41.Mg made more and larger tumorspheres. The mesenchymal‐like cells are more malignant than the epithelial‐like cells being the CF41.Mg the most malignant. This cell presented higher ZEB1 and ZEB2 and lower CDH1 gene expression. Finally, our results revealed that there is a positive correlation between ZEBs and the tumorsphere number and size. In conclusion, these findings support ZEB1 and ZEB2 as potential therapeutic targets for CMC cells, demonstrating a great potential of canine models for comparative and translational studies.